Tumor Suppressive Maspin-Sensitized Prostate Cancer to Drug Treatment Through Negative Regulating Androgen Receptor Expression - Tang, Sijie; Lian, Xueqi; Jiang, Jiajia; Cheng, Huiying; Guo, Jiaqian; Huang, Can; Meng, Hong; Li, Xiaohua (Frontiers in Cell and Developmental Biology, 2020)
Over activation of androgen receptor (AR)-mediated signal has been extensively implicated in prostate cancer (CaP) development, progression and recurrence, which makes it an attractive therapeutic target. Meanwhile, as an endogenous inhibitor of HDAC 1, tumor suppressive maspin was reported to sensitize drug-induced apoptosis and a better therapeutic outcome in CaP. But the relationship between AR and maspin remains unclear. In current study, treatment of 5’-Aza or MS-275 / Enzalutamide induced PARP cleavage and p-H2A.X in CaP cells with an increase of maspin expression but a decrease of AR. Then, treatment with protease inhibitor MG132 didn’t rescue the above drug-induced loss of AR. In addition, modulation of maspin expression by gene recombinant or siRNA technology showed the inverse correlation expression of maspin with AR, and consequently affecting the AR-regulated downstream gene transcription (e.g. NKX3.1, TMPRSS2). Bioinformatic analysis of the data extracted from NCBI GEO database also revealed the inverse correlation with low maspin expression but high AR level in advanced CaP. Furthermore, ChIP assay using anti-maspin antibody identified that a portion of AR promoter sequence was co-precipitated and presented in the immunoprecipitated complex. Finally, maspin–mediated repression of AR was induced by treatment of MS-275, which promoted Enzalutamide treatment efficacy with decrease of PSA expression in LNCaP and 22RV1 cells. Taken together, the data not only demonstrated maspin-mediated repression of AR to augment drug antitumor activity, but also provided in-depth support for combination of HDAC inhibitors with AR antagonist in CaP therapy.